Effectiveness of a family-centered behavioral and educational counselling approach to improve periodontal health of pregnant women: a randomized controlled trial - Pei Liu; Weiye Wen; Ka Fung Yu; Xiaoli Gao; Edward Chin Man Lo; May Chun Mei Wong (BMC, 2020)
Abstract Background Poor oral hygiene and high hormone levels during pregnancy can lead to a deterioration in periodontal health. This study assessed the effectiveness of a family-centered behavioral and educational counselling program on improving the periodontal health of women during pregnancy and postpartum. Methods A randomized controlled trial was conducted among pregnant women (10th-22nd gestational week) and their husbands. Participating families were randomized into test and control groups. Intervention in the test group included explanation of oral health education (OHE) pamphlets, oral hygiene instruction, individualized feedback, and proposed solutions to overcome barriers in self-care. Reinforcements were implemented in the 3rd trimester of pregnancy and six months postpartum. In the control group, only OHE pamphlets were distributed. The assessed outcomes were bleeding on probing (BOP), periodontal pocket (Poc), loss of clinical attachment (LoA), and Visible Plaque Index (VPI). The data collection was carried out at baseline (T0), in the 32nd gestational week (T1), and 12 months postpartum (T2). Results Altogether 589 pregnant women were recruited, and 369 attended all three visits (test:188; control:181). In the test group, the mean VPI score at T0 was 0.19, which decreased to 0.14 at T1 and 0.15 at T2. In the control group, the mean VPI decreased from 0.19 at T0 to 0.16 at T1, but increased to 0.22 at T2. A main effect of time and intervention and an interaction between time and intervention were detected (all p < 0.05), indicating that the intervention effect differed between T1 and T2. The test group showed a significantly greater decrease over time than the control group did. Similarly, the mean BOP% decreased more significantly over time in the test group (T0:57%, T1:46%, T2:35%) than in the control group (T0:58%, T1:52%, T2:46%). For Poc and LoA, there were improvements in both study groups at 12 months postpartum, compared with during pregnancy (p < 0.001). Conclusions Providing family-centered, behavioral, and educational counselling to pregnant women at an early stage of pregnancy and with reinforcements can improve their oral hygiene and reduce gingival inflammation. The effect can be sustained over an extended period and is greater than that of distributing oral health leaflets alone. Trial registration Clinicaltrials.gov , #NCT02937194. Registered 18 October 2016. Retrospectively registered, https://clinicaltrials.gov/ct2/show/NCT02937194?cond=Family-centered+oral+health+promotion+for+new+parents+and+their+infants&draw=2&rank=1